A History of the Pakistan Army : Wars and Insurrections - Cloughley, Brian (Karachi Oxford University Press, 1999)
"This is an in-depth study of the Pakistan Army. The scope of this book is wide because field marshals and generals ruled the country for many years. The author describes Pakistan's violent internal politics and erratic international relations in the context of military involvement, with the deep knowledge gained through long association with the country and its armed forces." "Pakistan's three wars with India are covered vividly, using unpublished sources and facts, and opinions from Indian as well as Pakistani accounts. The dramatic story of the country's resurrection under Zulfikar Ali Bhutto, after the disastrous war with India over Bangladesh, is told in an eminently readable way. The book also highlights the years of dictatorship that followed." "The later history of the army, while Pakistan was grappling with unaccustomed democracy and verging on anarchy, is told using close personal knowledge of many of the senior players."--Jacket.
Include Pictures, Bibliography and Index
Keywords: Pakistan. Army -- Politics and government